Bank Behavior in Developing Countries : Evidence from East Africa - Podpiera, Richard (IMF Working Papers; Working Paper ;, 2005)
We analyze the structure, performance, and role of banking systems in the three member countries of the East African Community-Kenya, Tanzania, and Uganda-against the backdrop of recent financial sector reforms. Focusing on the behavior of different types of banks, we find no support for the argument that the presence of large international banks would have an adverse effect on the effectiveness and efficiency of banking sectors in developing countries. International banks are generally more efficient and more active in lending than domestic banks. However, as suggested by the Kenyan experience, the presence of international banks may not lead to increased competition and provision of banking services if weak institutions are allowed to remain in the system.